The Effect of Integrated STEM Learning Models Based on Digital Technology on Improving Students' Digital Literacy - Ifa Safira; Siti Fatmah Hiola; Henny Sanulita; Nurina Happy; Tomi Apra Santosa; Unpris Yastanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the influence of digital technology-based integrated STEM learning models on improving students' digital literacy through a meta-analysis approach. Digital literacy is an essential competency in the era of the Industrial Revolution 4.0, and STEM learning that integrates digital technology is believed to be able to facilitate the strengthening of these skills. This study examined 20 scientific articles published in the period 2015–2024 and met the inclusion and methodological quality criteria. The analysis was carried out using JASP. The results of the meta-analysis showed that the digital-based STEM learning model had a significant influence on improving students' digital literacy, with an average effect size value of 0.78 which was included in the large category. Subanalysis based on education level indicates that the strongest influence occurs at the secondary education level. These findings imply that the development of STEM-based learning curricula and strategies that are integrated with digital technology needs to be continuously encouraged to strengthen students' readiness to face the challenges of the digital world.